Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Kottgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nature genetics, 2009)
Santhi Ganesh and colleagues report meta-analyses of genome-wide association studies of six erythrocyte traits within the CHARGE consortium, with replication in cohorts of the HaemGen consortium. They report 23 loci associated with a range of clinically relevant red blood cell traits. Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 × 10 −8 to 7 × 10 −86 ). Our findings include loci previously associated with these traits ( HBS1L-MYB , HFE , TMPRSS6 , TFR2 , SPTA1 ) as well as new associations ( EPO , TFRC , SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.